Configurações curriculares mediante o enfoque CTS: desafios a serem enfrentados na EJA - Muenchen, Cristiane (2006)
This research project analyses the challenges to be faced with the range of curricular interventions which aim to approach the interaction between Science, Technology and Society (CTS) through the setting down of contemporary themes, notably science and technology. Such curricular routings are marked by the approximation of the presuppositions of the Brazilian pedagogue Paulo Freire and references to the movement known as CTS. To achieve a critical reading of reality, a fundamental aspect of Freire, it is understood that a critical understanding of the interaction between CTS is becoming more and more essential, considering that the dynamics of contemporary society are becoming strongly conditioned by science and technology. In the context of such curricular interventions, is raised the problem of investigation: What are the possible challenges to be faced / investigated in the search for curricular configurations which look at the CTS approach through the laying out of socially relevant problems together with EJA? The objectives of the project are: to identify and discuss the position of EJA teachers in relation to the use, in class, of themes/problems of social relevance and to identify and discuss complications to be confronted in schools. This project is of a qualitative nature and the instruments used were: written registers in the form of diaries; questionnaires and interviews. As a synthesis of the results of the investigation, four categories are defined and discussed which constitute challenges to be faced: a) the excess of methodological reductionism, this being the teacher giving himself the role of program beater ; b) interdisciplinary work; c) the supposed student resistance to the themed approach and d) the development of polemic themes which involve local conflicts/contradictions.